Polyoxazoline hydrogels fabricated by stereolithography. (19th April 2022) - Brossier, Thomas; Benkhaled, Belkacem Tarek; Colpaert, Maxime; Volpi, Gael; Guillaume, Olivier; Blanquer, Sébastien; Lapinte, Vincent
Abstract : The development of hydrogel materials in additive manufacturing displaying stiff and strong mechanical properties while maintaining high water uptake remains a great challenge. Abstract : The development of hydrogel materials in additive manufacturing displaying stiff and strong mechanical properties while maintaining high water uptake remains a great challenge. Taking advantage of the versatility of poly(oxazoline) (POx) chemistry and properties, we investigated in this article a new generation of POx hydrogels fabricated by stereolithography (SLA). A large range of photosensitive poly(2-methyl-2-oxazoline) resins were synthesized as hydrogel precursors for SLA photofabrication. Functionalization has been performed by direct di-methacrylation of POx terminal groups (MA2 POx n ) or by multi-methacrylation of poly(ethyleneimine) (PEI) units resulting from partial POx hydrolysis (MA m POx n –PEI p ). The length and the functionality of these UV-active macro-crosslinkers influence both the mechanical properties and the hydration behavior of the resulting hydrogels. The benefit of the layer-by-layer crosslinking of the POx resin during the vat photopolymerization allowed the fabrication of complex and well-defined 3D objects. The high-definition and high mechanical strength of these copolymers allow the fabrication of stiff and strong 3D hydrogels. The cytocompatibility test of the POx derivatives was conducted in solution and once the cells are encapsulated within 3D hydrogels. Finally, porous 3D scaffolds with gyroid architectures were built which provide opportunities for POx materials in tissue engineering applications.